Bronchoalveolar lavage cell analysis in patients with human immunodeficiency virus related diseases. Issue 4 (April 1989) - Plaza, V; Jiménez, P; Xaubet, A; Picado, C; Torres, A; Agustí, C; Agustí-Vidal, A
Abstract : The value of differential cell counts in bronchoalveolar lavage fluid in patients who were serologically positive for the human immunodeficiency virus (HIV) was studied in 30 patients with classified into four groups according to the severity of illness: (1) seven subjects with the AIDS related complex without clinical or radiological evidence of pulmonary infection; (2) eight patients with the AIDS related complex and pulmonary tuberculosis; (3) eight patients with AIDS and Pneumocystis carinii pneumonia; and (4) seven patients with AIDS, Pneumocystis carinii pneumonia, and severe respiratory failure. All four groups had a similar percentage of lymphocytes, significantly higher than that of a control group of 15 healthy volunteers. A significant increase in the percentage of neutrophils was observed in groups 2, 3, and 4. The lavage fluid differential cell count does not therefore appear to help in the differential diagnosis of pulmonary infections in HIV positive patients. The abnormal percentage of lymphocytes observed in some patients with the AIDS related complex without clinical evidence of pulmonary infection suggests that lung injury may exist before clinical or radiological abnormalities develop. This might be related to an immunological mechanism or might be caused by an undetected subclinical infection.